Analysis of Operational Key Performance Indicator and Management Control System on Employee Performance (Case Study: PT. Modular Panel Erecta) - Gunaryo, Natahsya Novalica (Dinasti International Journal of Economics, Finance & Accounting, 2025)
In a business environment, human resource effectiveness plays a critical role in ensuring the success of the company. PT Modular Panel Erecta, a construction company, faces the challenge of aligning employee performance with its strategic goals. Key Performance Indicators and Management Control Systems (MCS) are important instruments in improving employee performance and ensuring that they work in accordance with predetermined targets. This study aims to analyze the effect of KPI and SPM on employee performance at PT Modular Panel Erecta. The research method used is a quantitative approach with surveys and interviews. Data was collected through questionnaires distributed to 30 employees selected using purposive sampling. Data analysis techniques include validity, reliability, and multiple linear regression tests to measure the relationship between KPI’s, SPM, and employee performance. The results of the study are expected to show that effective KPI implementation and an optimal management control system have a significant influence on increasing employee productivity and work efficiency. This study is expected to contribute to academics in the field of management accounting as well as to practitioners in improving the effectiveness of measuring and controlling employee performance, especially in the construction sector which faces complex challenges in labor management.